2004
DOI: 10.1103/physrevb.70.144410
|View full text |Cite
|
Sign up to set email alerts
|

Valence-sensitive determination ofCr3+andCe3+

Abstract: Magnetization-and susceptibility measurements are used as a method to determine the number density of the photorefractive centers Ce 3+ and Cr 3+ in Sr 0.61 Ba 0.39 Nb 2 O 6 (SBN61). The number densities n Ce 3+ = 0.73͑1͒ ·10 20 cm −3 and n Cr 3+ = 1.58͑8͒ ·10 20 cm −3 were determined for crystals doped with 1.6 wt.% Ce and 20000 ppm Cr, respectively. Frequency dependent susceptibility measurements in the temperature range 3-10 K on SBN61: Ce show that the spin-lattice relaxation in this compound is dominated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 21 publications
0
17
0
Order By: Relevance
“…Figure shows the UV/vis and FTIR spectra of SNP in methanol. The optical absorption spectrum of SNP displays two resonances at 393 and 520 nm assigned as the 7e ← 6e [π*(NO) ← 3d xz,yz ] and 7e ← 2b 2 [π*(NO) ← 3d xy ] transitions, respectively. , The UV/vis spectrum was obtained using a JASCO V-630 spectrometer with 1 nm resolution. The solvent-subtracted FTIR spectrum of SNP in methanol shows peaks corresponding to the nitrosyl stretch (ν NO ) and the cyanide stretches (ν CN ) centered at 1909 cm −1 (ε = ∫ε v d v = 3.3 × 10 4 M −1 cm −2 ) and 2145 cm −1 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure shows the UV/vis and FTIR spectra of SNP in methanol. The optical absorption spectrum of SNP displays two resonances at 393 and 520 nm assigned as the 7e ← 6e [π*(NO) ← 3d xz,yz ] and 7e ← 2b 2 [π*(NO) ← 3d xy ] transitions, respectively. , The UV/vis spectrum was obtained using a JASCO V-630 spectrometer with 1 nm resolution. The solvent-subtracted FTIR spectrum of SNP in methanol shows peaks corresponding to the nitrosyl stretch (ν NO ) and the cyanide stretches (ν CN ) centered at 1909 cm −1 (ε = ∫ε v d v = 3.3 × 10 4 M −1 cm −2 ) and 2145 cm −1 .…”
Section: Methodsmentioning
confidence: 99%
“…Given its possible uses, photoinduced linkage isomerism in SNP has garnered intense experimental and theoretical attention over the past decades as summarized in several recent reviews. ,, The experimental study of photoinduced linkage isomerism has mainly focused on the solid state where the metastable species can be trapped at low temperatures and subsequently characterized with steady-state spectroscopic and structural probes. , An exception to this is work by Schaniel et al where nanosecond transient absorption experiments on SNP in aqueous solutions detected the formation of MS2 with a lifetime of ∼110 ns . Experiments photoexciting aqueous solutions of SNP with continuous wave radiation have shown the formation of several dissociation products including the nitrosyl radical (NO·), cyanide ion (CN − ), [Fe III (CN) 5 (H 2 O)] 2− , and Prussian blue (PB). Theoretical works have calculated the electronic absorption spectra of the GS, MS1, and MS2 species and have considered the energetics of photoinduced linkage isomerism occurring on a multidimensional potential energy surface. , The theoretical studies along with the trapping of the linkage isomers using light of different wavelengths have suggested that the formation of MS1 and MS2 requires more than one photon depending on the experimental temperature. , …”
Section: Introductionmentioning
confidence: 99%
“…The metastable linkage isomers can be evidenced by the shift of the ν NO stretching vibration, and the population is determined by the decrease of the ν NO band . In the UV–vis spectral range population of MS1 and MS2 leads to a decrease of the absorption bands of the GS and the appearance of new absorption bands characteristic for the metastable states . The energy barriers (activation energy) separating the metastable states from the ground state and the energetic positions of the metastable states can be determined by DSC .…”
Section: Introductionmentioning
confidence: 99%
“…Several types of solid-state photomagnetic switches have been reported that differ in the mechanism by which specific electronic features of the metal ion are optically manipulated. Examples are represented by (i) light-induced excited spinstate trapping (LIESST), which involves reversible switching between spin states of Fe or Fe III spin crossover compounds, [5][6][7] (ii) ligand-driven light-induced spin-change (LD-LISC), in which photoisomerization of, for example, a stilbenoid ligand triggers the spin crossover of an Fe or Fe III center, 10,12 (iii) metal-to-ligand charge-transfer pro-moted by light irradiation in valence tautomeric systems such as nitroprusside [13][14][15][16] and Co or Mn II semiquinone complexes. 20,23 Another type of switchable magnetic material is represented by various types of heterobimetallic Prussian Blue (PB) analogues, in which the interplay between the two different adjacent metal ions is crucial for the observation of photoinduced phenomena.…”
Section: Introductionmentioning
confidence: 99%